HOW FISHES LIVE (Author: Peter Whitehead) - Prescott, John H. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1977)
Peter Whitehead. HOW FISHES LIVE. London: Elsevier Phaidon, 1975. 160 pp. $11.95.